Admixture and introgression obscure evolutionary patterns in lesser whitethroat complex (Curruca curruca; Passeriformes; Aves) - Raziyeh Abdilzadeh; Stefan Prost; Mansour Aliabadian; Arya Shafaeipour; Fumin Lei; Aleem Ahmed Khan; Urban Olsson (Journal of Avian Biology)
Determining the limits of species is still a major area of contention, particularly when diagnostic differentiating characters are subtle and there is a contradiction between morphological and genetic data. The lesser whitethroat (LWT) complex Curruca curruca represents an interesting study system to address this issue. Here, we use phylogeny‐, admixture‐ and principal component analysis‐ (PCA‐) based analyses on whole‐genome sequence data of the parapatric LWT taxa C. c. curruca, C. c. halimodendri, C. c. zagrossiensis and C. c. althaea to investigate the prevalence and importance of gene flow in a geographical area where morphological evidence suggests a clinal transition between populations. The results suggest that LWT populations of the Zagros Mts zagrossiensis may represent a lineage historically diverged from topotypical curruca, the two lineages later coming into secondary contact with extensive gene flow as a result. There is no evidence of a hybrid zone or cline between zagrossiensis and althaea in the Zagros Mts. On the other hand, there is evidence for gene flow between althaea and halimodendri. The results also show possible evidence of admixture from other populations in the LWT complex, extralimital to the sampled area, but the nature of this needs to be evaluated based on a larger data set.